Dynamic Security Exchange Scheduling Model for Business Workflow Based on Queuing Theory in Cloud Computing. (28th August 2020) - Xu, Rongbin; Wu, Jianguo; Cheng, Yongliang; Liu, Zhiqiang; Lin, Yuanmo; Xie, Ying
Abstract : With the rapid development of e-business, large volume of business processes need to be handled in a constrained time. There is always a security issue related to on-time completion in many applications in the economic fields. So, how to effectively manage and organize business processes became very important. By using cloud computing, instance-intensive processes can be handled more effectively by applying just-right virtual machines. Hence, the management of cloud resources became an important issue that many researchers focus on to fully utilize the advantage of cloud. In this paper, we mainly discuss the queuing theory and put forward our novel dynamic process scheduling model based on queuing theory, which is named M / G / k / l -P for business processes. This model can solve the issue of allocating appropriate number of cloud resources based on the number of tasks and execution stages to ensure whether the numbers of cloud resources are sufficient and adequate or not, which can improve the security issue for business process. The service discipline in our model can provide a dynamic process by setting different priorities to improve the experience of users. Evaluations prove that the queuing model of M / G / k / l -P can work very well for business workflow scheduling.